SINERGISITAS TRI PUSAT PENDIDIKAN DALAM MENCEGAH PERILAKU MENYIMPANG REMAJA DI DESA PRENDUAN KECAMATAN PRAGAAN KABUPATEN SUMENEP - Ashvina Kaisazallavana; Faizun Najah (Jurnal Binagogik, 2025)
The The background of this research is that education in Indonesia has progressed since gaining independence, with the main focus being to develop individual potential through families, schools and communities. The aim of this research is to determine the forms and efforts to overcome adolescent deviant behavior through Islamic religious education in Prenduan Village, Pragaan District, Sumenep Regency. This research uses a qualitative method with a descriptive approach that tends towards data analysis. The subjects of this research were the community, institutions and families from Prenduan village. The data collection techniques used are observation, interviews and documentation. The results of this research in Prenduan village show that Islamic religious education plays an important role in preventing deviant behavior among teenagers in Prenduan village.